ANALISIS PENDAPAT YUSUF QARDHAWI DAN ALI JUM’AH TENTANG HUKUM BUNGA BANK - Jati Riwi Maliastuti; Tedi Kholiluddin (TASAMUH, 2020)
ABSTRACT The opinions of scholars regarding bank interest are quite diverse, which are forbidden and permissible. Based on these conditions, two types of banking emerged, conventional and sharia. This study is to analyze the opinions of Yusuf Qardhawi and Ali Jum'ah about bank interest. This type of research is qualitative with a literature study approach. The aim is to compare the opinions of Yusuf Qardhawi and Ali Jum'ah about the law of bank interest. The conclusion of this research is that Yusuf Qardhawi firmly states that bank interest is the same as usury which is haram punished at any time. Ali Jum'ah was careful not to generalize that bank interest was the same as usury. In some cases, transactions in non-Muslim countries are permitted and riba (interest) from the transaction process is punished lawfully. The implication of the opinion of the two figures is that those who follow Yusuf Qardhawi's opinion will refuse to deal with or make transactions with conventional banks because bank interest includes usury. Followers of this opinion can choose Islamic banks as an option for transactions. Meanwhile, those who follow Ali Jum'ah's opinion have alternatives to transacting in conventional banks or Islamic banks. Especially with the condition of the Indonesian state which is not a formally Islamic state. Islamic values become the spirit for the formulation of policy regulations. Keywords: Bank Interest, Riba, Bank Interest Law ABSTRAK Pendapat ulama tentang bunga bank cukup beragam, yang mengharamkan dan membolehkan. Berdasarkan kondisi tersebut, muncul dua jenis perbankan, konvensional dan syariah. Penelitian ini untuk menganalisis pendapat Yusuf Qardhawi dan Ali Jum’ah tentang bunga bank. Jenis penelitian adalah kualitatif dengan pendekatan studi pustaka. Tujuan untuk membandingkan pendapat Yusuf Qardhawi dan Ali Jum’ah tentang hukum bunga bank. Kesimpulan dari penelitian ini adalah, Yusuf Qardhawi dengan tegas menyatakan bahwa bunga bank sama dengan riba yang sampai kapan pun akan dihukumi haram. Ali Jum’ah dengan hati-hati tidak menggeneralisasi bahwa bunga bank sama dengan riba. Dalam beberapa kasus, transaksi di negara non muslim dibolehkan dan riba (bunga) dari proses transaksi itu dihukumi halal. Implikasi dari pendapat kedua tokoh adalah bagi yang mengikuti pendapat Yusuf Qardhawi, akan menolak berhubungan atau bertransaksi dengan bank konvensional karena bunga bank termasuk riba. Pengikut pendapat ini bisa memilih bank syariah sebagai pilihan untuk bertransaksi. Sementara yang mengikuti pendapat Ali Jum’ah memiliki alternatif untuk bertransaksi di bank konvensional atau bank syariah. Terlebih dengan kondisi negara Indonesia yang bukan negara Islam secara formal. Nilai-nilai Islam menjadi spirit bagi penyusunan regulasi kebijakan. Kata Kunci: Bunga Bank, Riba, Hukum Bunga Bank